Effect of DC-DC converter switching frequency on the performance of solar PV system - Srinivas, P.; P.Swapna, Dr.; C.S.S.Anupama, Dr. (International Journal of Engineering and Technology, 2019)
The performance of Photo Voltaic (PV) system depends on how effectively the impedance matching is maintained under climatic changes i.e. change in insolation and temperature. The Perturb and Observe (P&O) and Incremental Conductance (InC) type classical Maximum Power Point Tracking (MPPT) controllers with boost converter are used to maintain the desired impedance matching. The switching frequency of boost converter does play an important role in the overall performance of solar system. Due to the change in the switching frequency, various parameters such as settling time, peak over shoot, steady state response, MPPT voltage, MPPT current, maximum power and output voltage values are affected. The influence of these time domain specifications on the performance of the photovoltaic system with modification of above controllers is discussed in this paper. MATLAB/SIMULINK is used for simulation studies of solar PV system with modified InC and P&O controllers. The performance of the modified InC controller over P&O controller at different switching frequencies in transient, steady-state and dynamic responses, related to ripple, power loss, tracking speed and overshoot have been analyzed.